(untitled) (Bangladesh Pharmaceutical Journal, 2025)
Poor sensitivity of pathogenic bacteria to bacteria is a serious health issue worldwide specially in the developing and underdeveloped countries making greater concern to the scientists. This study followed the CLSI (Clinical and Laboratory Standards Institute) guidelines 30, Kirby-Bauer disc diffusion method to test sensitivity. We analyzed the antibiotic sensitivity pattern of Escherichia coli and Salmonella typhi isolated from clinical samples, collected from two hospitals of Dhaka, Bangladesh. The sensitivity of twelve different single antibiotics (cefepime, cefotaxime, chloramphenicol, ciprofloxacin, nitrofurantoin, meropenem, imipenem, amikacin, gentamicin, azithromycin, tetracycline, fosfomycin), and two combinations (piperacillin-tazobactam and amoxicillin-clavulanate) were evaluated against E. coli and S. typhi isolates. E. coli isolates showed significantly less susceptibility than S. typhi isolates to the antibiotics tested. Three antibiotics showed significant effectiveness against E. coli isolates, (chloramphenicol, nitrofurantoin, and fosfomycin). Ciprofloxacin was the least effective antibiotic to S. typhi isolates (only 20% isolates showed sensitivity). 85% E. coli isolates were MDR (Multi Drug Resistant), whereas only 5% S. typhi isolates were MDR. The highest MAR (Multiple Antibiotic Resistance) index value among E. coli isolates was 0.86, whereas highest value among S. typhi isolates was 0.21. The lowest MAR value among E. coli isolates was 0.21, whereas two S. typhi isolates had MAR value of zero (0). Almost all the single and combination antibiotics demonstrated poor sensitivity to the E. coli and S. typhi isolates. Thus, it makes infections much harder to treat and makes other medical procedures and treatment, such as surgery, caesarean sections and cancer therapy, much riskier. Bangladesh Pharmaceutical Journal 28(1): 94-104, 2025 (January)